The Influence of Marketing Strategy and Lifestyle on the Purchase Decision of Mitsubishi Xpander at PT. Dipo Internasional Pahala Otomotif - Sri Rezeki; Ihdina Gustina (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
This study aims to determine the effect of Marketing Strategies and Lifestyle on Purchasing Decisions at PT. Dipo Internasional Pahala Otomotif. The population in this study are all consumers who have made purchases at PT. Dipo Internasional Pahala Otomotif in 2019. By using the Slovin formula with an error rate of 10%, a total sample of 91 respondents was obtained. The research analysis shows that the Marketing Strategy and Lifestyle partially and simultaneously positively and significantly affect Purchasing Decisions at PT. Dipo Internasional Pahala Otomotif. The results of this study are supported by the value of R square (R2) which means that the Marketing Strategies and Lifestyle have an effect on the Purchasing Division at PT. Dipo Internasional Pahala Otomotif. While the remaining is affected by other factors originating from outside this research model such as price discounts, advertising, consumer attitudes, consumer confidence, and brand image.